1992
DOI: 10.1111/j.1530-0277.1992.tb01883.x
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Evidence for Alcohol Binding and Dehydration in Phospholipid and Ganglioside Micelles

Abstract: We theorize that intoxicants and modern anesthetics bind at the membrane-water interface and displace (dehydrate) bound water molecules by breaking the hydrogen bonds. We tested this hypothesis by examining the effect of butanol on the binding of water to the polar regions of lipids in reversed micelles. Understanding the mechanisms of intoxication requires studies in physiologically relevant systems such as systems containing sialoglycoconjugates, especially gangliosides, which concentrate in the synapses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…It was also shown that water undergoes polar interactions with (CH3)3N+. The binding of ethanol at the lipid-water interface may perturb the inner hydration shell around the lipid headgroup, based on the release of bound water observed with FTIR (Chiou et al, 1992;Yurttas et al, 1992) and the decreased Avq for bound D2O in the current work. At the same time, however, it is possible that the increase in the area per lipid caused by ethanol binding (discussed below) may lead to an overall increase in the amount of partly ordered water associated with the lipid-water interface.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It was also shown that water undergoes polar interactions with (CH3)3N+. The binding of ethanol at the lipid-water interface may perturb the inner hydration shell around the lipid headgroup, based on the release of bound water observed with FTIR (Chiou et al, 1992;Yurttas et al, 1992) and the decreased Avq for bound D2O in the current work. At the same time, however, it is possible that the increase in the area per lipid caused by ethanol binding (discussed below) may lead to an overall increase in the amount of partly ordered water associated with the lipid-water interface.…”
Section: Discussionmentioning
confidence: 68%
“…Also, a radio tracer study measuring the partitioning of ethanol between a membrane pellet and aqueous supernatant found that mouse brain synaptosomes had a partition coefficient 60 times higher than that for La phase dipalmitoylphosphatidylcholine (DPPC) bilayers (Sarasua et al, 1989), suggesting that in synaptosomes ethanol may be able to bind to a variety of polar groups, including those of proteins and carbohydrate groups. Fourier transform infrared (FTIR) studies of inverted micelles of DPPC and gangliosides (water in carbon tetrachloride) suggest that ethanol displaces some bound water at the micellar surface (Chiou et al, 1992;Yurttas et al, 1992). Data by Klemm and co-workers [reviewed in Klemm (1990)] suggest that the acute effects of ethanol in the brain could be mediated by changes in the hydrogen or electrostatic bonding between gangliosidic sialic acid and receptor proteins, due to the replacement of water with ethanol.…”
mentioning
confidence: 99%
“…To answer this question, 5 g of BDH silica hydration forces, which may be the cause for the intoxication. Spectroscopic analysis of lipids membranes treated with was contacted with a 10 04 M pyridine solution of pH 6.0 for 20 min, and the supernatant solution was subjected to alcohols show evidence for the displacement of bound water (38,39). According to the force data obtained in the present UV analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that ethanol can decrease the evidence for nonlinear structure in the EEG invites speculation as to how such findings might relate to theories of the actions of ethanol on brain and behavior. Recent theories suggest that ethanol may act on both proteins and lipids in neuronal membranes (Mander et al, 1985;Besson et al, 1989;Chiou et al, 1990;Klemm, 1990;Weight, 1992;Yurttas et al, 1992;Grant, 1994;Isobe et al, 1994;Li et al, 1994;Peoples et al, 1996). How such physical changes in the cellular milieu lead to intoxication at the behavioral and electrophysiological level, especially at lower doses, has not yet been elaborated.…”
Section: Discussionmentioning
confidence: 99%